STUDENTS' HONEST ATTITUDES IN SCIENCE LEARNING AT SMPN 15 TANJUNGPINANG: A MIXED METHOD STUDY - Sarkity, Dios; Eries Fahri Ardi Saragih, Jeffris; Oprasmani, Elfa (Program Studi Pendidikan IPA FKIP Universitas Jember, 2025)
In the digital era, character education—particularly the value of honesty—is essential to prevent the misuse of knowledge for unethical purposes. This study explores students’ honesty within Integrated Science learning at SMP Negeri 15 Tanjungpinang, focusing on how honest behavior manifests in the learning process and the factors influencing students’ honesty or dishonesty. Employing a mixed-methods approach with a sequential explanatory design, the study collected quantitative data through questionnaires from 105 students selected via stratified random sampling, and qualitative data through interviews with selected students based on their honesty levels. The results showed that students’ overall honesty was categorized as good, with an average percentage score of 75.40%. The highest-rated indicator was “dislike lying,” while the lowest was “reporting things truthfully.” However, 42% of students fell into the “fairly honest” or “dishonest” categories, indicating a need for ongoing character development. Qualitative findings revealed three main reasons for dishonest behavior: peer influence, lack of fear of sanctions, and pressure to achieve good grades. These findings suggest that students' dishonest actions are shaped by social, psychological, and academic factors. The study concludes that promoting honesty requires a holistic strategy involving curriculum integration, teacher role modeling, consistent disciplinary measures, and support from families. This research implies that effective character education must engage all stakeholders in creating an ethical school culture and supportive learning environment